الحافظ أبو زرعة (ت : ٨٢٦هـ) ومنهجه في دفع التعارض بطريق النسخ من خلال كتاب "طرح التثريب " باب الأضحية أنموذجاً - مجيد, کامه ران أورحمان; على, م. په یام جافر (Sulaimani Journal for Humanities, 2024)
This paper will deal with one of the most important issues in the science of Hadith, namely the issue of abrogation. As is common among the scholars of hadith, abrogating occurs when two hadiths are different in meaning and do not coexist. At this time, one of the two hadiths are valid, according to the conditions set for it, and the other is not valid and is deleted. The paper will discusse the role of Abu Zur'ah, as a Kurdish and hadith scholar, who has been able to play a decisive role in the debate between the jurist and the scholars of hadith, when there are two hadiths with different meanings. This is be appeared from from the study of an article in his book (Tarh al-Tathrib) as an example.